Organizacje wspomagające Milicję Obywatelską w powiecie zielonogórskim w latach 1945-1950 = Organizations aiding the Civic Militia in Zielona Góra county between the years 1945-1950 - Krystians, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The following article discusses the role of organizations aiding and supplementing the activities of the Civic Militia (MO, abbreviated from Milicja Obywatelska). It describes both the organizedforms of MO's support (the Civic Guard, the Voluntary Reserve of the Civic Militia) and an effort has been made to depict the means and methods of using secret collaborators by the MO and the effects of their work, which, as to this moment, have remained not-so-well recognised.
Keywords: Ochotnicza Rezerwa Milicji Obywatelskiej (ORMO); Milicja Obywatelska; Zielona Góra (okręg) - historia; historia; 1945-1950